Cytogenetics in multiple myeloma patients progressing into extramedullary disease - Besse, Lenka; Sedlarikova, Lenka; Greslikova, Henrieta; Kupska, Renata; Almasi, Martina; Penka, Miroslav; Jelinek, Tomas; Pour, Ludek; Adam, Zdenek; Kuglik, Petr; Krejci, Marta; Hajek, Roman; et al. (European journal of haematology, 2016)
BACKGROUND: Extramedullary disease in multiple myeloma patients is an uncommon event occurring either at the time of diagnosis, or during disease progression/relapse. This manifestation is frequently associated with poor outcome and resistance to treatment. We evaluated chromosomal alterations of plasma cells of multiple myeloma patients with extramedullary relapse, either in the bone marrow (BM) or at extramedullary sites, and in previous BM collection by interphase fluorescence in situ hybridization. MATERIAL AND METHODS: Thirty-one patients [25 BM plasma cells (BMPCs), 18 extramedullary tumor plasma cells], of which 12 had paired samples of BM and extramedullary plasma cells and 14 had previous collection of BM, were investigated for the presence of chromosomal aberrations (CHAs): del(17)(p13), del(13)(q14), 14q32 disruption, t(4;14)(p16;q32), t(14;16)(q32;q23), gain(1)(q21), and hyperdiploidy status. RESULTS: Overall, in unrelated samples, t(4;14) was more prevalent in extramedullary plasma cells, and hyperdiploidy was more frequent in BMPCs. In paired samples, there was a higher frequency of del(13)(q14) and 14q32 disruption in BMPCs. Frequency of all studied CHAs was higher in BMPCs of extramedullary patients than in their previous sample collection. CONCLUSION: These data show that plasma cells harbor more aberrations during their transformation into extramedullary form.
Keywords: Neoplasm Metastasis; Male; progrese nemoci; hybridizace in situ fluorescenční; Neoplasm Staging; chromozomální aberace; multiple myeloma; Adult; cytogenetics; Aged; dospělí; translokace genetická; mužské pohlaví; senioři; Disease Progression; Multiple Myeloma; Chromosome Aberrations; senioři nad 80 let; lidé; ženské pohlaví; Biomarkers, Tumor; Humans; Bone Marrow; extramedullary relapse; kostní dřeň; Aged, 80 and over; Translocation, Genetic; In Situ Hybridization, Fluorescence; mnohočetný myelom; metastázy nádorů; Female; lidé středního věku; staging nádorů; nádorové biomarkery; Middle Aged